PEMANFAATAN LIMBAH DARAH SAPI DAN KIAMBANG SEBAGAI PUPUK RAMAH LINGKUNGAN UNTUK MENDUKUNG PERTANIAN LAHAN GAMBUT YANG BERKELANJUTAN - HASTIN ERNAWATI; NUR CHUSNUL CHOTIMAH; SUSI KRESNATITA; GUSTI IRYA ICHRIANI (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2015)
ABSTRACTA Farming system adopted by farmers in Sub-District Kalampangan is very dependent agricultural systems within organic fertilizer. The use of in organic fertilizers continuously providea considerable impact on the surroundingenvironment. Nutrient the soilare bound by the molecules of chemical fertilizers so the top soi lregenerationprocess can not to be done.One alternativesolutionthat is proposed is the use of fertilizers derived from localresources around, the cow blood waste from slaughter houses and swamp plant sgiant salvinia (Salvinia molesta).Trouble shooting methods in this service activities were 1) education and training composting of cow blood-giantsalvinia 2) demonstration plot to show the prove of greatness of cow blood-giant salvinia compost to the plants3) mentoring and coaching partner farmers. The results showed that cow blood and giant salvinia potentially beusedas contained in an environmentally friendly organic fertilizer fo able crops grownon peat. Thefertilizershouldbe developedso thatfarmerscanbea superior productin order to meetone of thecomponents neededto initiatethechangefromconventional farming systemstoorganic farming systems.Keywords : cow blood waste, giant salvinia, compost, organic fertilizer, organic farming